PHLOGOPITE AND HORNBLENDE IN SPINEL HARZBURGITES FROM THE MID-ATLANTIC RIDGE: MINERAL ASSEMBLAGES AND ORIGIN - Bazylev, B.A.; Silantyev, S.A.; Kononkova, N.N. (Ofioliti, 1999)
Phlogopite in mid-oceanic ridge peridotites was detected mainly as inclusions in spinel and rarely as discrete grains from ultramafic cumulates (Arai et al., 1997). Phlogopite and biotite were also found in oceanic gabbro (Cannat et al., 1992; Cannat and Casey, 1995; Silantyev, 1998). In most cases, hornblende is associated with phlogopite. Origin of these minerals in oceanic peridotites and gabbro is now under discussion. In our investigations, phlogopites were detected in spinel harzburgites from a number of localities within the Mid-Atlantic Ridge - at 15oN and 35oN areas. The compositional variety of phlogopites is maximal in harzburgites containing thin gabbroic veins from dredge 68 (16-th cruise of r/v “Akademic Boris Petrov”) located in the west slope of the rift valley at 14o49’N. Since associated minerals are often preserved in these rocks, it is possible to address the problem of the origin of this association. In gabbro veins and of their contact with peridotite, phlogopite forms tables with clear pleochroism. Phlogopite is characterized by high TiO2 (1.5-3.0 wt%), low Mg# (65-85) and low Cr2O3 (0.0-0.65 wt%). Rare small grains of high-Ti spinel (1.1 wt% TiO2) are present at its rims. In peridotites, phlogopite occurs as small (< 0.1 mm) plates in narrow shear zones near the contact with gabbros. Phlogopite is usually colorless or with hardly recognizable pleochroism; it is Ti-rich (2.0-2.3 wt% TiO2), relatively Crpoor (0.1-0.7 wt% Cr2O3), and Mg-rich (Mg# 93.2-93.7). Orthopyroxene and hornblende are associated with phlogopite, both having elevated TiO2 contents (1.3-2.1 and 0.14- 0.23 wt%, respectively). Ti-poor phlogopite (0.3-0.6 wt% TiO2) has been found in a similar textural position. Ti-poor phlogopite has the same ranges of Cr2O3 contents and Mg#, and it is associated with Ti-poor hornblende and orthopyroxene (TiO2 = 0.4-0.7 and 0.02-0.05 wt%, respectively), and sometimes with plagioclase. Ti-rich spinel (TiO2 up to 0.37 wt%) seems to take part in these associations. Phlogopite has also been found in harzburgites that do not show relations with gabbros. Phlogopite occurs either as discrete grains (0.1-0.4 mm) along shear zones, or single grains in olivine, or in contact with spinel, or as plates replacing orthopyroxene along cleavage. It shows low TiO2 (0.04-0.4 wt%), high Mg# (90.1-94.7) and high Cr2O3 (0.65-1.6 wt%) content. No silicates associated with phlogopite are present, and associated spinels are enriched in iron and sometimes in titanium (up to 0.27 wt% TiO2). The orthopyroxenes associated with phlogopite and hornblende are commonly characterized by low Al2O3, Cr2O3 and CaO (1.0-1.8 wt%, 0.18-0.70 wt% and 0.35-0.80 wt%, respectively). Hornblende has high K2O (0.22-0.50 wt%) and is represented by edenitic and pargasitic hornblendes according to Leake’s nomenclature. In harzburgites, clinopyroxene usually is not in contact with phlogopite and rarely with hornblende. According to Wells’s geothermometer, the crystallization of the phlogopite-hornblende mineral association took place at 870-1000oC. Distribution of Ti between coexisting phases is consistent with evaluated coefficients (Ionov et al., 1997) and indicates TiO2 liquid contents in the range of 0.56-1.40 wt% for the Ti-rich mineral association. Therefore, its crystallization possibly took place from fractionated melts. Origin of the low-Ti association is disputable. On the basis of mineral compositions, the low-Ti association is inferred to have crystallized at the same temperature range. The two minerals associations can be detected at one millimeter scale. The preferred hypothesis is crystallization of the low-Ti mineral association from a fluid phase, which was exsolved from the liquid. Alternatively, crystallization derived from extremely low-Ti melts (below 0.24 wt% TiO2). However, some phlogopites show TiO2 contents as low as 0.10 wt%, which lead to unrealistically low calculated TiO2 contents in the liquid (0.04 wt%). Crystallization of the phlogopite-hornblende mineral association in spinel harzburgites from Capo Verde FZ area took place after solidification of peridotites, mainly along shear zones, which was a place for segregation of residual differentiated melts and related fluids. In other places of Mid-Ocean Ridges, a shearing event under the same temperature conditions is associated with the development of plagioclase-bearing mineral associations, where only in rare cases edenitic-pargasitic hornblende occurs (Cannat and Seyler, 1995). This difference is related to the compositions of fractionated melts that interacted with the mantle peridotites, so that generation of phlogopite is restricted to areas of geochemical anomalies along Mid-Atlantic Ridge. Some gap between two areas of water silicate generation in mantle peridotites under MOR seems to exist. In a first one, outlined above, the source of water should be of juvenile origin. The second area is connected with deep penetration of seawater into the lithosphere. In the latter case, the temperature hardly exceeds 800-820oC, phlogopite does not crystallize, hornblende is represented mostly by tremolite, rarely by edenite or edenitic hornblende, and never by pargasitic hornblende. Recrystallized orthopyroxene in this process is characterized by extra-low calcium contents (CaO = 0.15-0.20 wt%). This work was supported by the Russian Foundation for Basic Research grant 97-05-64842.